A one-pot synthesis of novel cyclic ketene dithioacetals from Nef-isocyanide-Perkow adduct. (2nd November 2017) - Yavari, Issa; Saffarian, Hamed; Naeimabadi, Maryam
ABSTRACT: A novel synthesis of cyclic ketene dithioacetals through the reaction between phosphorous-based ketenimines [generated in situ from Nef-isocyanide-Perkow reaction], cyclic 1, 3-dicarbonyl compounds, and carbon disulfide at room temperature, in moderate to good yields (65–80%), is described. GRAPHICAL ABSTRACT: